Experimental Study on the Effect of Air Flow Rate Variation on the Performance of a Three-Phase Airlift Pump With an Injector Angle of 15° - Maulana, Rizki; Fajarningrum, Nurmala Dyah; Hayati, Nur; Saleh, Arif Rahman (FLYWHEEL : Jurnal Teknik Mesin Untirta, 2025)
Rivers in Indonesia are heavily polluted, with the main source of pollution coming from industrial waste, including poorly managed mining activities. The airlift pump is used to lift liquid or sediment from a water reservoir that has a lower elevation through a vertical pipe that is partially submerged in the water. This research aims to determine the effect of air flow rate on the performance of the airlift pump during operation under three-phase flow conditions. The performance of the airlift pump is examined through several parameters: superficial velocity, effectiveness, efficiency, and flow patterns. In this study, a tank measuring 50x50x50 cm and a 2.54 m tall acrylic pipe are used as the riser to facilitate the lifting of three-phase flow to the separator component that separates the three phases located at the end of the riser. With a submergence ratio of ¾ h or 1.905 m and using variations of air flow rates of 30, 40, 50, and 60 LPM. The results of this research confirm that increasing air flow rate enhances superficial velocity in all three phases. At air flow rates of 30-50 LPM, the efficiency increases from 4.18 ×10-3 % and peaks at 5.14 ×10-3 %. At 60 LPM, it decreases to 4.88 ×10-3 %. The highest effectiveness reaches 1.281 at an air flow rate of 60 LPM. The optimal flow pattern occurs in slug flow and transitions towards churn flow.